Genetic analyses of chromosome 12 loci in Crohn's disease. Issue 6 (1st December 2000) - Lesage, S; Zouali, H; Colombel, J-F; Belaiche, J; Cézard, J-P; Tysk, C; Almer, S; Gassull, M; Binder, V; Chamaillard, M; Le Gall, I; Thomas, G; et al.
Abstract : BACKGROUND AND AIMS: Inflammatory bowel disease (IBD) includes ulcerative colitis and Crohn's disease, both of which are multifactorial diseases involving the interaction of genetic and environmental factors. A region on chromosome 12 centred around the marker locus D12S83 has previously been associated with IBD predisposition. The aim of the study was to investigate this genetic region in an independent panel of European families affected by Crohn's disease. METHODS: A sample of 95 families with two or more affected relatives and 75 simplex nuclear families were genotyped for 19 microsatellite loci located on chromosome 12. A search for linkage and linkage disequilibrium was performed using non-parametric two point and multipoint analyses with the Analyze and Genehunter packages. RESULTS: No evidence of linkage or linkage disequilibrium was observed for any of the marker loci, including D12S83 (p=0.35 for the two point linkage test). Multipoint linkage analysis also failed to reveal positive linkage on chromosome 12. Power calculations allowed us to reject the hypothesis that the genetic region of chromosome 12 centred on D12S83 contains a susceptibility locus with a relative risk (λs ) equal to or greater than 2.0 in these families. CONCLUSION: Failure to detect linkage or linkage disequilibrium in these families suggests that the chromosome 12 locus previously reported to be associated with genetic predisposition to IBD does not play a role in all European family samples. This observation is compatible with heterogeneity in the genetic basis of susceptibility to the disease and/or exposure to various environmental factors among Caucasian families.